Earnings Management in Banking Sector: Pre-Post Analysis of NFRS - Sanjel, Deepak (Campion Journal of Multidisciplinary Research and Explorer, 2025)
The study examines the impact of the implementation of Nepal Financial Reporting Standards (NFRS) on earnings management practices in Nepalese commercial banks. Drawing on agency theory, it investigates whether the adoption of NFRS has effectively enhanced financial transparency and reduced earnings manipulation, particularly through discretionary loan loss provisions (DLLP). The research utilizes a two-stage regression model on panel data covering 331 bank-year observations from 2010/11 to 2023/24. The findings indicate that earnings management significantly declined following NFRS implementation, suggesting improved transparency in financial reporting. Moreover, while higher earnings before interest and tax (EBIT) reduce DLLP, greater total loans and Tier 1 capital ratios are associated with increased earnings management. Macroeconomic factors like GDP and credit growth show no significant impact. Diagnostic testing supports the use of a random effects model, which confirms the robustness of the results. The study contributes to the literature on financial reporting in emerging economies by providing empirical evidence that principle-based standards like NFRS can enhance the quality of financial disclosures in the banking sector.